The accessibility of visually impaired people to museums and art through ICTs - Vasilakou , Paraskevi; Mineiko , Sofia; Hasioti , Theopisti Marina; Gavriilidou , Zoe; Drigas, Athanasios (Technium Social Sciences Journal, 2022)
Human’s involvement with culture is a vital part of his life, but what happens when someone is blind or visually impaired (VI) and how Information and Communication Technologies (ICTs) help the access to cultural locations? The difficulties and limitations that blind and visually impaired (BVI) persons face while visiting museums or art exhibitions are of high importance. These limitations concern both the access to the location and the perception of the exhibits. This bibliographic research is divided into four main parts. In the first part of our paper we will analyze the difficulties that these people face as visitors in art exhibitions and how their disabilities affect an autonomous visit. Afterwards, we will refer to the importance of the disability arts when combined with ICTs. In the next part, we will mention the projects that are already applied or those for which efforts have been made globally for their implementation. These will be accompanied by recorded feedback from blind and visually impaired visitors. Finally, we will make a scheduled visit to the Tactual Museum of Athens in order to collect material on practices used in their exhibition and we shall record reactions from visually impaired visitors.